EIB Working Papers 2019/09 - The impact of international financial institutions on small and medium enterprises - Petriček, Matic; Rop, Anton; Gereben, Áron; Winkler, Adalbert (European Investment Bank, 2021)
IFIs provide funding for SMEs, but what impact does this actually have on these firms? This working paper assesses the impact of funding by the EIB on the performance of more than 5,000 SMEs in eight countries in Central and Eastern Europe during 2008-2014. Using propensity score matching and difference-in-difference estimation exercises, it indicates that EIB lending has had a positive effect on employment, revenues and profitability. This holds whether or not the economy is in a period of crisis or recovery.